Comparative Efficacy of Insecticides and Plant Extracts For Management of Chilcv Disease In Relation to Epidemiology (Global Journal of Science Frontier Research, 2018)
Three Chilli varieties/lines including 7-ph, Biaddy and Tatapuri were sown to check the comparative efficacy of different insecticides and plant extracts. Three insecticides including Imidacloprid, Bifenthrin and acetameprid and three different plant extracts including onion extract, Garlic extract and parthenium were evaluated against Chilli leaf curl virus (ChiLCV) and whitefly. Bifenthrin was very much effective in reducing whitefly population while Acetameprid was least effective as compared to control.Garlic extract at 5% concentration was very much effective in reducing whitefly population while parthenium extract at 5% concentration was least effective compared to control. Correlation of environ-mental factors (maximum and minimum temperature, relative humidity and rainfall) chiLCV disease incidence % was also determined. There was a significant correlation of environmental variables with ChiLCV disease incidence %. The use of Bifenthrin (10%EC) proves to be significant option in case of epidemiological occurrence of environmental variables followed by acetamaprid (20%SL) and imidacloprid (25%WP) respectively.
Keywords: chilli leaf curl virus; (chiLCV); correlation; insecticides; plant extracts and disease incidence